Cover Crop Grazing Effects on Soil Compaction Indicators in Western and Central Kansas - L. M. Simon; A. K. Obour; J. D. Holman; S. K. Johnson; K. L. Roozeboom (Kansas Agricultural Experiment Station Research Reports, 2022)
Grazing cover crops (CCs) on no-till (NT) croplands in western and central Kansas could increase the profitability of crop production in these water-limited environments. However, little information exists about potential soil compaction associated with grazing CCs in these cropping systems. From 2019 to 2021, two studies investigated the effects of grazing CCs on soil bulk density and penetration resistance in NT cropping systems. At the Kansas State University HB Ranch near Brownell, KS, CCs grazed with yearling heifers were compared to ungrazed CCs and fallow under NT or occasional tillage (OT). In another study, CCs grazed with yearlings or cow-calf pairs were compared to ungrazed CCs across seven site-years on producer fields in western Kansas (Alexander and Hays) and central Kansas (Marquette 1 and 2). Soil bulk density and penetration resistance measurements were made at the time of subsequent grain crop planting following CCs. At Brownell, CC management, tillage, and their interaction had no significant effect (P>0.05) on soil bulk density. Across years, bulk densities with fallow, ungrazed CCs, and grazed CCs were 1.11, 1.15, and 1.15 g/cm3at the 0- to 2-inch soil depth, respectively. Soil bulk densities with NT and OT were 1.14 and 1.14 g/cm3at the 0- to 2-inch soil depth, respectively. Similarly, CC grazing had no significant effect on soil bulk density and penetration resistance across the seven on-farm sites-years. At the western Kansas locations, soil bulk density averaged 1.23 g/cm3at the 0- to 2-inch soil depth with grazed or ungrazed CCs. At the central Kansas locations, soil bulk density averaged 1.31 and 1.36 g/cm3at the 0- to 2-inch soil depth for grazed and ungrazed CCs, respectively. Bulk density measured at 2- to 6-inch depth was not different between grazed and ungrazed CC in either study. At Alexander, penetration resistance was 0.52 and 0.52 MPa with grazed and ungrazed CCs, respectively. Penetration resistance was 0.36 and 0.34 MPa with grazed and ungrazed CCs, respectively, at Marquette 1. Results showed that grazing CCs never increased soil bulk density or penetration resistance compared to ungrazed CCs. Based on these findings, grazing CCs on NT fields can be a strategy for producers to balance profitability and soil health.
Keywords: cover crops; grazing; soil compaction